The Experience of Death and Expatriation in Yayiyt Malik Bin Al- Rib – Study in the tools of art composition – - Al- Qarni, Aqaila Mohammed (Journal of Humanities & Social Sciences, 2020)
Yayiyt Ibn al- Rib represents a unique artistic experience in Arabic poetry; It is customary for the poet to lament someone else who loves and chooses it, Either he laments himself at death, and in the hour of embarrassment and difficulty, it is a departure from the norm, and a pattern contrary to the way of poets and their methods in this art!The poet was able to express, with the skill of a capable maker, obsessions himself and the severity of his pain, and the intensity of his nostalgia, through the artistic composition, and the poetic colors he adopted at the level of language, Imagination and rhythm. This study, through its three axes, seeks to reveal its dimensions, and the impact of all this on the success of the experiment, and its impact on the hearts of its recipients. It is based on the technical curriculum. Among the most important results that were achieved: the disclosure of the impact of the experience that the poet experienced a painful reality, on his artistic experience in its various formations and manifestations.
Keywords: poetic experience; Malik bin Al-Rayeb; self-pity; nostalgia; alienation